Protection Of Human Rights According To Islamic Law - Tolhah Toha Nawawi (Sean Institute, 2024)
This study seeks to examine the perspectives of Islamic law on the safeguarding of human rights within the framework of social and moral equity. This research examines the Islamic religion's primary sources, such as the Koran, Hadith, and interpretations by prominent scholars, to determine how Islamic religious law supports and safeguards human rights within Muslim culture. The research employs qualitative examination of religious texts, contextual interpretation of verses from the Koran and associated hadiths, and literature reviews about the perspectives of ulama and modern thinkers on matters pertaining to human rights. This research also entails a comparative analysis of the principles of safeguarding human rights in Islamic jurisprudence. The aim of this research is to gain a comprehensive understanding of how Islamic beliefs relate to the protection of human rights and whether they align with universally accepted international norms. Furthermore, this study seeks to discern any potential disparities between the notion of human rights in Islamic jurisprudence and the practical understandings prevalent in contemporary Muslim communities. It also endeavors to explore strategies for bridging these divergences.